Goldenhar syndrome associated with an epibulbar dermoid: Case Report: Sindrome de Goldenhar asociado con un dermoide epibulbar: Reporte de Caso - Mamani Maquera, Diego J. (2022)
We present the case of a 7-year-old male child with Goldenhar syndrome associated with an epibulbar choristoma. The patient presents a homogeneous tumor, rounded in shape, with well-defined borders, of a soft consistency, vascularized, approximately 9x10 mm, yellowish-white in color, adhered to the sclera and cornea, with hairy formations on its surface, located at the level of the sclerocorneal limbus of the temporal-lower quadrant of his right eye. The histopathology study showed the presence of hair follicles and sebaceous glands, immersed in a stroma of fibrous connective tissue with a superficial squamous-type lining, which defined the diagnosis of limbar epibulbar dermoid. Conjunctivaplasty was performed to cover the scleral defect and use amniotic membrane to cover the corneal and scleral defect. The limbar epibulbar dermoid is the most common type of conjunctival choristoma and should be considered in the differential diagnosis of pediatric epibulbar tumors.